Desenvolvimento de cartilha para operações bancárias digitais seguras - D'ORIA, Luigi Mário; PEREIRA, Marcelo Assim (126, 2022)
Recentemente tem havido um aumento significativo nas fraudes contra os usuários do sistema bancário e foi observado que a grande maioria delas poderia ser evitada com a alteração de alguns hábitos e ações dos usuários. Este trabalho apresenta uma cartilha sobre como se prevenir dos principais golpes aplicados nos pagamentos em comércios tradicionais e digitais, terminais de autoatendimento bancário, cartões bancários e mesmo em aplicativos de mensagem instantânea. Trata-se de uma pesquisa aplicada, composta por pesquisa bibliográfica para a discussão das contribuições de autores da área e pesquisa experimental, com vistas ao desenvolvimento de uma cartilha. Espera-se que quem leia esta cartilha tenha maior acesso a formas de evitar esses golpes.

Recently there has been a significant increase in fraud against users of the banking system and it was observed that the vast majority of them could be avoided by changing some habits and actions of users. This work presents a booklet on how to prevent the main scams applied to payments in traditional and digital commerce, automatic teller machine, bank cards and even instant messaging applications. This is an applied research, composed of bibliographic research to discuss the contributions of authors in the area and experimental research, with a view to developing a booklet. It is hoped that those who read this booklet will have greater access to ways to avoid these scams

Recently there has been a significant increase in fraud against users of the banking system and it was observed that the vast majority of them could be avoided by changing some habits and actions of users. This work presents a booklet on how to prevent the main scams applied to payments in traditional and digital commerce, automatic teller machine, bank cards and even instant messaging applications. This is an applied research, composed of bibliographic research to discuss the contributions of authors in the area and experimental research, with a view to developing a booklet. It is hoped that those who read this booklet will have greater access to ways to avoid these scams.
Keywords: Bancos; Gestão da informação; Serviços de informação; Informação - segurança; Informação e Comunicação